‘Buffers’ against crime? Exploring the roles and limitations of positive relationships among women in prison - Crittenden, Courtney A. (2013)
A considerable amount of research focuses on the detrimental influence that relationships pose for women offenders while relatively little attention has been given to the potential positive impact of relationships in their lives. This study investigates how women offenders’ positive relationships work as ‘buffers’ against their criminal involvement, as well as why some positive influences do not elicit long-term change in women. We examine various forms of relationships (both romantic and non-romantic) that female offenders develop and explore the mechanisms by which these relationships might influence their behavior. Life history interviews conducted with 60 incarcerated women revealed that women’s family members, friends, significant others, and children provided support, social capital, motivation, and opportunities which can buffer women from criminal behavior, but that women’s drug use, disadvantage, interest in, pride or shame, and desire to make positive changes limited the effectiveness of these relationships